1997
DOI: 10.2989/025776197784160938
|View full text |Cite
|
Sign up to set email alerts
|

Management of South African dusky kob Argyrosomus japonicus (Sciaenidae) based on per-recruit models

Abstract: The dusky kob Argyrosomus japonicus is an important linefish species that is abundant in South African waters between Cape Agulhas and the M~ambique border. The juveniles «I 070 mm) occur inshore, where they are targeted by surf-zone and estuarine anglers, and the adults are caught mainly beyond the surf by recreational and commercial linefishermen. Yield-per-recruit (YIR) and spawner biomass-per-recruit (SBIR) models were applied to the South African dusky kob stock, with accommodation for different inshore (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 12 publications
2
37
1
Order By: Relevance
“…The stock status of the dusky kob and white steenbras is believed to be collapsed, while the stock status of the spotted grunter is considered over-exploited (Cowley et al 2009). The most recent research available on the adult dusky kob population suggests that it is between 1 and 4.5% of the non-impacted (original) population, a level that could be below the recovery threshold for this species (Griffiths, 1997). The populations of these species have declined radically during the last decade due to the popularity of the Sundays River Estuary for recreational fishing.…”
Section: Introductionmentioning
confidence: 99%
“…The stock status of the dusky kob and white steenbras is believed to be collapsed, while the stock status of the spotted grunter is considered over-exploited (Cowley et al 2009). The most recent research available on the adult dusky kob population suggests that it is between 1 and 4.5% of the non-impacted (original) population, a level that could be below the recovery threshold for this species (Griffiths, 1997). The populations of these species have declined radically during the last decade due to the popularity of the Sundays River Estuary for recreational fishing.…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that dusky kob attain sexual maturity at a much larger size than silver kob (Griffiths, 1996b(Griffiths, , 1997b and that drumming muscles are used during courtship in sciaenid species (Griffiths, 1997c), unidirectional hybridization could be explained by hypothesizing that large dusky kob males may occasionally out-compete silver kob males by gaining access to oestrous silver kob females. Griffiths (1996b) found that sexually mature dusky kob males (but not females) could be found throughout the distribution range of the species in South African waters and Griffiths (1997b) reported a tendency for silver kob to have a skewed sex-ratio in favour of females, which could result in increased opportunities for dusky kob males to compete with silver kob males.…”
Section: Squaretailmentioning
confidence: 99%
“…Although silver kob seems to have entered a recovery phase due to drastic efforts to reduce quotas in the commercial linefishery (Winker et al, 2013), wild stocks of both species have been severely depleted due to overfishing (Griffiths, 1997a, c). Specifically, spawner biomass-perrecruit has been estimated at less than 5% and 12.5% of pristine values for dusky kob and silver kob, respectively (Griffiths, 1997c), which urges a prompt evaluation of the current conservation status of these species. Following the decline of wild stocks and growing local demand for these species in the seafood market, kob farming has been initiated in the emerging South African aquaculture sector (DAFF, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is one of South Africa's most sought-after commercial, recreational and subsistence fishery species (Brouwer et al 1997, Griffiths 1997a. A. japonicus can live in excess of 40 yr and attain a body mass of 75 kg; they sexually mature at approximately 100 cm (Griffiths & Heemstra 1995, Griffiths 1996.…”
Section: Introductionmentioning
confidence: 99%